2019
DOI: 10.1590/1809-6891v20e-55176
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Content in Cheeses: Suitability to the Voluntary Agreement and Labeling

Abstract: This study was done to establish the sodium concentration in the cheeses marketed in the western border region of the Rio Grande do Sul. A total of 30 cheese samples (grated Parmesan, Mozzarella, Prato and Artisanal) were collected from different brands and lots. After analyzing them under atomic emission spectroscopy, in quadruplicate, the sodium levels were ascertained. From the quantification of the sodium content significant differences were noted among the lots of all the cheese brands assessed. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Another brazilian study estimated the sodium concentration in cheeses and their compliance with the voluntary agreement. The authors reported that 77.8% of the brands failed to satisfy the limit established for sodium reduction agreed upon by the Ministry of Health and Brazilian Association of Food Industries, making allowances for a period for adaptation (Ugalde, Mello, Centenaro, & Furlan, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Another brazilian study estimated the sodium concentration in cheeses and their compliance with the voluntary agreement. The authors reported that 77.8% of the brands failed to satisfy the limit established for sodium reduction agreed upon by the Ministry of Health and Brazilian Association of Food Industries, making allowances for a period for adaptation (Ugalde, Mello, Centenaro, & Furlan, 2019).…”
Section: Resultsmentioning
confidence: 99%